Teaching Russian in Uzbek groups in universities - Isakova Ravshana Karimjanovna; Tursunova Inobat Mirkamilovna (Zien Journals, 2022)
This article describes in detail the methods of teaching Russian in Uzbek groups in universities, the general didactic principles of teaching Russian, the principles of Russian as a science, science and interdisciplinary relations in teaching Russian.
Keywords: russian language teaching; didactic principle; interdisciplinary communication; russian language methodology